Acute respiratory distress syndrome in Plasmodium falciparum malaria - (:unkn) unknown (My University, 2009)
Acute respiratory distress syndrome (ARDS) as a complication of malaria infection is rare but with a very high mortality rate. We report the case of a patient who developed high fever, then respiratory distress during a trip to Haiti who was admitted to our hospital and diagnosed with malaria. During recovery the patient developed ARDS in the hospital.
Keywords: Humans; Middle Aged; Turkey; Male; Respiratory Distress Syndrome; Haiti; Malaria, Falciparum; Travel